2018
DOI: 10.1002/cc.20323
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Community College Completion Rates by Securing Students’ Basic Needs

Abstract: Food and housing insecurities are serious challenges confronting community college students. This chapter reviews the evidence on prevalence and correlates of basic needs insecurity and discusses institutional actions to support students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 11 publications
1
64
0
Order By: Relevance
“…First, in this study, food-secure students exhibited better academic performance as represented by APS scores and higher GPAs, suggesting that having a secure source of food can be beneficial to overall college success. This is consistent with previous literature, as food-insecure college students are less likely to show positive academic performance, including attending class and maintaining a high GPA (6, 8, 33, 66). Specifically, this finding is in line with previous multicampus food-insecurity work, in which food insecurity is reported as directly related to lower student GPA (38).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…First, in this study, food-secure students exhibited better academic performance as represented by APS scores and higher GPAs, suggesting that having a secure source of food can be beneficial to overall college success. This is consistent with previous literature, as food-insecure college students are less likely to show positive academic performance, including attending class and maintaining a high GPA (6, 8, 33, 66). Specifically, this finding is in line with previous multicampus food-insecurity work, in which food insecurity is reported as directly related to lower student GPA (38).…”
Section: Discussionsupporting
confidence: 92%
“…Most college food insecurity studies are based on individual universities with few large-scale food insecurity studies completed across multiple states and regions (31–33). Research thus far, however, generally fails to capture students from 4-y institutions, and instead focuses primarily on community colleges (32, 33), with few exceptions (34). However, most students in the United States are enrolled in 4-y institutions (35), and the demographics and lifestyles of these 4-y students often differ from those who are enrolled at community colleges (36, 37), making it important to investigate food insecurity among multiple 4-y institutions as well.…”
Section: Introductionmentioning
confidence: 99%
“…Food insecurity has been associated with increased behavioral problems and emotional burdens that can impact a student’s success in academia [ 14 ]. In particular in the college population, food-insecure students are less likely to attend and perform well in class and more likely to withdraw from a course all together [ 30 , 50 ]. Other studies confirm this association through GPA and have found that students with a GPA above 3.1 were 60% less likely to be food-insecure [ 25 ] with another reporting food-insecure students having a mean GPA of 3.1 vs. 3.4 in food secure students [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, the study reveals the impact food insecurity can have on students’ behaviors with increased money expenditure and coping strategies, and decreased academic progress in food-insecure students. The behaviors of young adult college students are essential for success and degree retention, with numerous students leaving college without successful degree completion, causing a financial burden to both the university and the student [ 50 ]. Providing for the basic needs of students and fostering positive behaviors would promote student success and are important avenues for addressing food insecurity on college campuses.…”
Section: Discussionmentioning
confidence: 99%
“…Even though as faculty, we are considering various points of access to education for LGBTQIA+ students at CCSF, we must not only consider the safe spaces that the students need—resource centers, classrooms, ADA compliant and gender‐inclusive buildings, trained faculty and staff—but other basic needs like access to food (Goldrick‐Rab, ). For the past 2 years, the Queer Resource Center (QRC), which has a faculty advisor but is student‐run, has opted to put the small stipend they receive from Associated Students Services to hosting a free food pantry instead of holding a Lavender Graduation ceremony.…”
Section: Accreditation Woes and Economic Boom: Ccsf Lgbtqia+ Studentsmentioning
confidence: 99%